PERBEDAAN HASIL BELAJAR EKONOMI MENGGUNAKAN MODEL INQUIRY DENGAN KONVENSIONAL DAN AKTIVITAS BELAJAR SISWA KELAS X MAN KOTO BERAPAK KABUPATEN PESISIR SELATAN - Mastayelni Mastayelni; Syamwil Syamwil (Program Magister Pendidikan Ekonomi (S2), 2016)
This study aims to determinedifferences in learning outcomes of the economics using of model inquirywith a conventional,andlearning activity of students,and theinteraction between thelearning modelwithlearning activity of studentsof class XMANKotoBerapakSouth Coastal District.This research is aquasiexperimentwith a population ofstudents of classX1 and X2 the academic year2015/2016amounted to54students. Data were collected using a questionnaireactivityandachievement test.Datawere analyzed usingAnovatwolanes(Two Ways OfANOVA). The result of the study showed that students learning outcomes increased after the application of inquiry learning model, which amounted to80.67 Keywords: Inquiry learning model, learning activity, and interaction